Electrochemical Evaluation of Biologically Modified Carbon Paste Electrode with Cyclic Voltammetric Technique - Zaib,Maria (2019)
A carbon paste electrode has been modified with a red algal species of Porphyridium cruentum, and the characterization of its electro catalytic activity has been done with cyclic voltammetric studies of the potassium ferricyanide (K3(Fe(CN)6)) system. In order to highlight the electrode's stable and fast response to the (Fe(CN)6)3-/(Fe(CN)6)4- redox couple, experiments were also conducted with a bare carbon paste electrode. FTIR spectra revealed the functional moieties of the bare and modified electrodes. The electrochemical surface area and surface coverage capacity were calculated for both electrodes. The effect of the scan rate helped to evaluate the nature of the electrode process, electron transfer mechanism, and kinetic parameters (rate constant and charge transfer coefficient).